Diversidade de caranguejos e estrutura populacional de Uca cumulanta Crane, 1943 (Decapoda: Brachyura: Ocypodidae) em um manguezal no Nordeste brasileiro - Pillon, Clarissa Ferreira (2014)
The aim of this study was to describe the richness and composition of crabs (Crustacea: Brachyura) from four stations in the Rio Formoso mangrove, state of Pernambuco, and then characterize the population structure of the fiddler crab Uca cumulanta. Samplings were carried out monthly from March 2009 to April 2010, covering all microhabitats. The air temperature, burrow´s temperature and burrow´s salinity were measured and correlated to abundance of species, were also compared among sampling sites and between dry and rainy periods. To determine patterns in the structure and composition of the brachyuran taxocenosis were performed multivariate analyzes and calculated the diversity indices total and for each station. Were recorded 7.544 brachyuran crabs belonging to 23 species, 12 genera and seven families. The families with greater richness were Ocypodidae and Panopeidae. In relation to stations the greatest richness was recorded in station 4 (18 species) followed by station 1 (15 species), station 2 (13 species) and station 3 (8 species) of crabs was observed. The highest abundance was found in station 1 (2.242) individuals, followed by station 3 (2.039), station 2 (1.820) and station 4 (1.443). Uca thayeri and U. leptodactylus were the most abundant species. The highest Shannon diversity occurred in station 4, station 2 and 3 had the lowest evenness. The taxocenosis of crabs showed a clear spatial pattern with high dissimilarity between stations, greatest between stations 3 and 4 (72.01 %). Environmental variables did not influence the abundance of species and it also did not varied among sampling stations, however, varied between dry and rainy period. The results showed that the diversity of crabs in the mangrove areas of Rio Formoso was expressive, however, with low diversity indices due to dominance of some species, the collection area has great spatial heterogeneity and environmental variables had no influence on the abundance of crabs at this site. In order to characterize the population structure of Uca cumulanta, based on same data sampling described before, the average size of males and females, the frequency distribution by size classes (carapace width - CW), sex ratio, ovigerous females and handedness in the population were analyzed. A total of 346 individuals were collected: 211 males and 135 females. There was no significant difference in the average size of carapace width of males (7.86 ± 1.07 mm) and females (7.88 ± 1.15 mm). The size frequency distribution was normal and unimodal for both males and females. The overall sex-ratio (1.56: 1) shows a higher frequency of males. Only five ovigerous females were found and a population was predominant right-handed. In general, population of U. cumulanta is stable and data was similar to those previously recorded for other species of the genus. Considering that most tropical mangroves were not well explored and there are many species to be discovered, this study will contribute to the knowledge of local taxocenosis and thus provide allowance for crab conservation and management of this estuarine area.